Publizistische Kontroversen über den Holocaust im Film - Thiele, Martina (UB Göttingen, 2002)
After the transmission of the US-American series Holocaust in 1979 there was talk of a "caesura in the Germans dealing with their National Socialism". But the series Holocaust (Marvin Chomsky, USA 1978) does not represent the only attempt to show the German crime committed against the Jews. Before and after the Holocaust-series came a large number of more or less successful German and international films and TV-productions, for example Morituri (Artur Brauner/Eugen York, Germany 1948), Night and Fog (Alain Resnais, France 1955), Mein Kampf (Erwin Leiser, Sveden 1960), Naked among wolfes (Frank Beyer, GDR 1963), Only one day (Egon Monk/Gunther R. Lys, FRG 1965), The Process (Eberhard Fechner, FRG 1984), Shoah (Claude Lanzmann, France 1985) and last but not least Schindler's list (Steven Spielberg, USA 1993). These films were vehemently discussed in the german press. The subject of this study are the structures and functions of the journalistic controversies which were caused by the films. The question is focused on the extend to which the Germans in East and West are willing to be confronted with their history and the role of the mass media as a mediator of historic consciousness. Siegfried Kracauer believes that a nations cinema reflects its mentality. If this is the case is it possible to discuss the National Socialism and Holocaust dialogue in terms of phases it has gone through since 1945? Or is it legitimate to dismiss the controversies, which were caused by the Holocaust-films as media hype and "shoah business"? This would insinuate that the films did not have any effect except for a short-term shock-effect. The above mentioned films differ immensely in terms of their conditions under which they were made and the resonance they evoked. But this discourse-analytic study of the journalistic controversies shows, that the arguments for and against Holocaust-films have remained practically unchanged in the past 50 years.
Keywords: controversies; debates; film; Holocaust; Holocaust; Mein Kampf; Morituri; naked among wolfes; night and fog; only one day; representation; Schindler's List; Shoah; Shoah; The Process; 070